The trespassers - Snyder, Zilpha Keatley (New York : New York., 1995)
Having trespassed and explored the empty Hutchinson mansion, which seems haunted by the presence of a long-dead young girl, sixth grader Neely and her little brother become regular visitors when emotionally disturbed Curtis Hutchinson moves in.
Keywords: Ghosts -- Fiction; Emotional problems -- Fiction